Quality of life in chronic kidney disease: a community perspective using world health organization quality of life: BREF questionnaire - Jacob, Sabitha R.; Kannan, Suthanthira; Raveendran, Rini; Wilson, Tom (International Journal Of Community Medicine And Public Health, 2020)
Background: The quality of life is an important assessment tool in improving the quality of care among chronic kidney diseases (CKD) especially in a palliative care setup. This study attempted to assess the quality of life of chronic kidney disease patients. Methods: This community based cross sectional study was conducted among 140 patients who were registered at palliative clinics in Malappuram District, Kerala using a standard tool for quality of life (QOL) in Malayalam version. Domain scores were analysed across clinic epidemiological factors. Results: Mean age of the study population was 53.99 (14.36%). Majority 73 (52.1%) were educated up to upper primary. The median duration of CKD was 4 years and ranged from 3 months to 22 years. 55.3% were undergoing dialysis 16.3% had renal transplantation. Hypertension was reported by 65% and diabetes by 50.7%. The highest score was obtained in the environmental and lowest in the psychological domain. Age below 40 years, male gender and provision of an income was associated with better QOL scores and perception scores. QOL was significantly higher in all domains among those who had undergone renal transplantation compared to those on hemodialysis. Conclusions: The status of renal transplantation and younger age group positively affected the good quality of life. Considering the cost of renal transplantation and post-transplant survival peritoneal dialysis could be promoted in low resource settings. Secondary prevention of hypertension and diabetes should be addressed at programme level to delay nephropathy.